Attention, Recall and Purchase: Experimental Evidence on Online News and Advertising - Tommaso M. Valletti; André Veiga (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We conduct an experiment where subjects read online news articles and are shown ads for brands next to those articles. Using eye-tracking technology, we measure the attention that each individual devotes to each article and ad. Then, respondents choose between cash or vouchers for the brands advertised. Attention to ads is a predictor both of willingness-to-pay for brands, and brand recall. The main predictors of attention include the type of news and the match between individual political preferences and the media outlet.
Keywords: M37; C91; L86; 330; online-advertising; experiments; attention; e-commerce; targeting